Testament of Tsutomu Sakuma - Sakuma, Tsutomu, 1879-1910.
English translation of a manuscript found in the pocket of Sakuma who died in a submarine sunk in maneuvers of the Japanese navy (kaigun) in Hiroshima Bay (1910 April 15). He assumed responsibility for the sinking and wrote of the valor of his crew.
Typewritten transcript .
Japanese naval officer.
Forms part of: Miscellaneous Manuscripts collection.
Collection material in English.
Keywords: Japan. -- Kaigun; Submarine disasters -- Japan; Hiroshima Bay (Japan); Naval officers, Japanese